Preparation of A Process And Project Maturity Model For An IT Company - Agata WOJCIECHOWSKA; Jacek STROJNY (Communications of International Proceedings, 2021)
The aim of the article is to develop a process and design maturity model adapted to the specifics of a medium-sized company operating in the IT industry and enabling the identification of key areas for improving its operations. The article contains a theory related to project management models and proes management models. It also presents the specifics of the IT industry and projects implemented in this industry. Due to the need to analyze the above objective and to create reliable research results, the AHP method and the qualitative method in the form of an interview with specialists and practitioners from the project management and process management industry were used. As a result of the research, a model was proposed that takes into account the necessary elements for the IT industry related to processes and projects. In the future, research should be developed in a practical direction, i.e. the proposed model should be verified on a larger sample and implemented in an IT company.
Keywords: Process Management Model; Project Management Model; IT Industry; IT Project.